Molecular and phenotypic profiling of colorectal cancer patients in West Africa reveals biological insights - Olusegun Isaac Alatise (Nature Portfolio, 2021)
Understanding the molecular and phenotypic profile of colorectal cancer (CRC) in West Africa is important for early detection and treatment. Here, the authors use a multigene next-generation sequencing panel to identify genomic differences in Nigerian CRCs compared to those from TCGA and MSKCC cohorts.